Physicochemical analysis and phytochemical screening of carabao mango (Mangifera indica) seed kernel oil. - Deniola, Emmanuel Gulangayan
Fats and oils, which mostly come from plants in the form of seed oils, are essential parts of the human diet. There several kinds of oils which have reported beneficial effects., Since mango seeds are considered wastes, the utilization of the oil from it my be of commercial importance. The charactristics of the mango seed kernel oil were identified to determine if it could be an alternative to the expensive cocoa butter. The results showed that the mango seed kernel has comparable amounts of stearic and oleic acid. However, it has a lower palmitic acid content than cocoa butter. The oil from the kernels of mature carabao mangoes was extracted using n-hexane as a solvent. The approximate crude fat yield from the solvent extraction was 6.1 percent while the soxhlet extraction using diethyl ether yielded 7.5 percent of oil. The carabao mango seed kernel oil has an acid value of 0.51 mg KOH/g oil, saponificationvalue of 252.63 mg KOH/g oil, iodine value of 44.84 I2/100g oil, and a peroxide value of 14.48 meq O2 / kg oil. The oil has a refractive index of 1.463 and its specific gravity is 0.897. Mango seed kernel oil is solid at room temperature. The determined melting point for the oil is 38.13 degrees centigrade. The phytochemical screening of the mago seed kernel oil detected the presence of phytochemicals such as terpenoids, flavonoids, saponins, tannins, alkaloids and as well as steroids. However, reducing sugars, anthraquinones and cardiac glycosides were not detected. The IR spctrum of the mango seed kernel oil showed that it has similarities with that of the corn oil. However, the spectra of the two oils revealed that mango seed kernel oil has a lower degree of unsaturation than corn oil. This supported by the fatty acid comosition of the mango seed kernel oil, showing that it is composed of 43.73 percent stearic acid, a saturated fatty acid and 39.81 percent oleic acid, a monounsaturated fatty acid. On the othe hand, literature suggests that corn oil is composed of 47.19 percent linoleic acid and 36.99 percent oleic acid, both of which are unsaturated fatty acids.